Berlin - Fulbrook, Mary 1951- (Cambridge University Press, 2025)
Now capital of the Federal Republic of Germany, Berlin rose from insignificant origins on swampy soil, becoming a city of immigrants over the ages. Through a series of ten vignettes, Mary Fulbrook discusses the periods and regimes that shaped its character - whether Prussian militarism; courtly culture and enlightenment; rapid industrialisation and expansion; ambitious imperialism; experiments with democracy; or repressive dictatorships of both right and left, dramatically evidenced in the violence of World War and genocide, and then in the Wall dividing Cold War Berlin. This book also presents Berlin's distinctive history as firmly rooted in specific places and sites. Statues and memorials have been erected and demolished, plaques displayed and displaced, and streets named and renamed in recurrent cycles of suppression or resurrection of heroes and remembrance of victims. This vivid and engaging introduction thus reveals Berlin's startling transformations and contested legacies through ten moments from critical points in its multi-layered history